2020
DOI: 10.1128/msphere.00637-20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Face Masks in Preventing Airborne Transmission of SARS-CoV-2

Abstract: Guidelines from the CDC and the WHO recommend the wearing of face masks to prevent the spread of coronavirus (CoV) disease 2019 (COVID-19); however, the protective efficiency of such masks against airborne transmission of infectious severe acute respiratory syndrome CoV-2 (SARS-CoV-2) droplets/aerosols is unknown. Here, we developed an airborne transmission simulator of infectious SARS-CoV-2-containing droplets/aerosols produced by human respiration and coughs and assessed the transmissibility of the infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
333
4
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(360 citation statements)
references
References 5 publications
18
333
4
5
Order By: Relevance
“…The N95 mask has the highest protective efficacy: approximately 80–90% reduction in virus intake. In contrast, cotton and surgical masks blocked more than 50% of the virus outward transmission, whereas the N95 masks showed approximately 90% protective efficacy [ 31 ]. The average filtration efficiency of single-layer fabrics and of layered combination was found to be 35% and 45%, respectively [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The N95 mask has the highest protective efficacy: approximately 80–90% reduction in virus intake. In contrast, cotton and surgical masks blocked more than 50% of the virus outward transmission, whereas the N95 masks showed approximately 90% protective efficacy [ 31 ]. The average filtration efficiency of single-layer fabrics and of layered combination was found to be 35% and 45%, respectively [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The masks were 60%–70% effective at protecting others and 50% effective at protecting the wearer. 10 The mechanism by which masks block viruses depends purely on the physical characteristics of the carrier droplet or aerosol and not the virus itself, so evidence for other viruses can be extended to SARS-COV-2 with careful consideration of the size of the droplets and aerosols involved. For instance, in a study of patients with documented infections with either seasonal coronaviruses or influenza virus, surgical masks blocked coronaviruses released into the air to undetectable levels and partially blocked influenza virus.…”
Section: Main Textmentioning
confidence: 99%
“…They found that three double-layers of any tested fabric could meet the pressure difference standards and particle filtration efficiency of graded masks. More recently, Ueki et al [4] tested two manikin heads in a biosafety level 3 box, exhaling droplets that were originally…”
Section: Introductionmentioning
confidence: 99%